2017
DOI: 10.23834/isrjournal.322734
|View full text |Cite
|
Sign up to set email alerts
|

Information and Communication Technologies (ICTs) and Corruption Level: Empirical Evidence from Panel Data Analysis

Abstract: In recent years, there have been great interest for solving corruption problems associated with public and private sector. On the other hand, nowadays the rapid development of technology related to transformation in the ICT technologies is observed from many sources in the literature. In this process, implementations of anticorruption policies have been helped by these technologies. In addition to this support, the empirical analyses on relationships between ICT and corruption are still scarce. In this regard,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…In a connected world, mobile wireless technology that is considered part of the technology infrastructure is associated with higher FDI inflows. Empirical studies show that the growth of mobile technology has a direct effect on FDI (Koyuncu and € Unver, 2016). In a study of Southeast European countries (SEEC), Dauti (2008) stated that the ICT infrastructure market is the main factor positively associated with FDI inflows, while other factors such as GDP growth, GDP per capita and GDP level have significantly negative effects on FDI inflows.…”
Section: Foreign Direct Investment (Fdi) and Digital Infrastructure (Di)mentioning
confidence: 99%
“…In a connected world, mobile wireless technology that is considered part of the technology infrastructure is associated with higher FDI inflows. Empirical studies show that the growth of mobile technology has a direct effect on FDI (Koyuncu and € Unver, 2016). In a study of Southeast European countries (SEEC), Dauti (2008) stated that the ICT infrastructure market is the main factor positively associated with FDI inflows, while other factors such as GDP growth, GDP per capita and GDP level have significantly negative effects on FDI inflows.…”
Section: Foreign Direct Investment (Fdi) and Digital Infrastructure (Di)mentioning
confidence: 99%
“…The gap level in the use of ICT in each province in Indonesia creates the gap on tax revenue of each province as well, so it is necessary to conduct research related to the correlation between the use of ICT on tax revenues at the provincial level in Indonesia. The author has adopts the concept from the research of Brun et al (2020), Hanrahan (2021), Koyuncu & Ünver (2017) for its provincial-level research in Indonesia. Through the tax decentralization system which causes differences in tax collection authority, this research is divided into 3 models, namely the central tax revenue model, the provincial tax revenue model, and the district/city tax revenue model.…”
Section: Introductionmentioning
confidence: 99%
“…Several research has been done relates to the use of ICT on tax revenues which measured across regions or across countries, such as: Koyuncu & Ünver (2017), the results of their research shows that the use of ICT increases tax revenues throughout the country, then Brun et al (2020) indicates that the influence of ICT readiness had a positive but not significant impact on tax revenue, then Adegboye et al (2022) revealed that the influence of ICT on the tax ratio is very positive, but has a threshold and after crossing the threshold, the impact will be negative. The results of Hanrahan (2021) actually defined that digitalization can have a negative impact on tax revenues in developed countries with high ICT utilization conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Teorik ve ampirik pek çok çalışmanın da ortaya koyduğu üzere BIT'in e-devlet hizmetlerinde kullanımının önemli sosyal, ekonomik ve idari faydaları da bulunmaktadır. Bu faydaları şu şekilde özetlemek mümkündür (Warkentin vd, 2002;Davison vd, 2005;Hung vd 2006, Huang, 2007Demirbaş vd, 2012;Bannister & Connolly, 2015;Sun vd, 2015;Koyuncu & Ünver, 2017);  Kamu hizmetlerine tek noktadan ve daha hızlı erişim imkanının sağlanması  Dijital bölünmelerin ortadan kaldırılması  Online tartışma, oylama ve bilgi paylaşımı ortamı kurularak katılımcı vatandaş ve duyarlı devlet modelinin oluşturulması  Katma değeri yüksek ve çeşitlendirilebilir kamu hizmetleri sağlanması  Kamu hizmetlerinin birim maliyetlerinin düşürülmesi  Kaynak kullanımında verimliliğin ve etkinliğin arttırılması  Kamu yönetiminde etkin denetimin sağlanması  Devletin ve kamu hizmetleri sunucularının daha şeffaf ve hesap verebilir düzeye ulaştırılması  Kamu sektöründe yolsuzlukların azaltılması  Kamu (devlet) yönetimine modern görünüm kazandırılması  Devletin vatandaş ve firmaların taleplerinde daha duyarlı olabilmesi  Vatandaşın devlete olan güveninin arttırılması E-devlet, karmaşık kurum içi ve kurum dışı (harici) kullanıcılardan oluşan bütünleşik bir yapıdır. Genel olarak bu bütünleşik yapı pek çok çalışmada olduğu gibi dört farklı ağ ile açıklanmaktadır (Siau & Long, 2005;Heeks, 2006;Martins ve Popovic, 2014).…”
unclassified